Feminism and Female Character Representation in the Works of English Women Writers: A Comparative Analysis of Charlotte Brontë and Jane Austen (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This analytical article explores the emergence and early development of feminist ideas in the works of prominent English women writers, focusing on Charlotte Brontë and Jane Austen. While writing in different literary periods and styles, both authors portray the inner world, challenges, and aspirations of women in patriarchal society. Through a comparative study of selected novels, the article examines the social, psychological, and ideological aspects of female characters, showing how Brontë and Austen contributed to early feminist discourse. The analysis highlights their literary strategies, narrative techniques, and the ways their heroines sought intellectual, emotional, and personal autonomy.